Gender inequality and precarious work: exploring the impact of unions through the gender and work database - Jackson, Andrew (Winnipeg, 2004)
"Unions clearly have a positive impact upon the wages of women and upon earnings gaps by gender, and increasing union coverage has clear potential to raise the wages and related employment outcomes of women in precarious jobs. The above analysis has shown that union coverage is positive for the wages of women and for greater wage equality between women and men in the public sector, but is neutral in the private sector as a whole. This is because there is a high degree of occupational segregation between women and men. When the impact of unions on female-dominated occupations in the private sector is examined, the effect is seen to be one of raising wages for lower paid women and closing pay gaps between women and men. Unfortunately, union coverage among women in private services, especially lower paid women, is very low -- and good unionized jobs for women in public and social services are increasingly at risk due to outsourcing and privatization. The challenge for unions is to increase organizing efforts among women, especially low paid women in private services, to place even greater emphasis on equity issues in collective bargaining, and to shape the overall structure of employment through changes in public policies. Ultimately, success will lie in organizing enough women in low-pay occupations to make a real difference in the economics of low-wage industries, in maintaining and increasing good jobs in public and social services, and in promoting pay and employment equity legislation. These are, of course, daunting challenges." (Extract from the conclusion)